(untitled) (Teología, 2018)
This article presents the results of a theological investigation focused on the case study of the parish, Natividad del Señor (Nativity of the Lord), in the Archdiocese of Rosario, Argentina, and is part of the second cycle of research conducted by the Urban Theology research group based at the Pontifical Catholic University of Argentina in its School of Theology. The general framework is based on the interdisciplinary orientation of urban theology and a conscious effort at interaction between the fields of theology, spirituality, and pastoral theology within the Argentine school of theology and focusing on practices of spirituality. For the empirical gathering of data and theological interpretation of the case—particularly the interpretation of this parish’s practice of the Way of the Cross—the mediation of the qualitative method was utilized. This method privileges the known subject’s point of view without disregarding the perspective of the researcher and his or her own disciplinary specificity. The article is organized into two parts. The first presents the case study in its fundamental elements: the parish, Natividad del Señor; the figure of Ignacio Peries; and the religious phenomenon of the Way of the Cross. The second attempts a theological reading of the Way of the Cross from three perspectives: the presence of the crowd; the comparison of the Good Shepherd and the sheep (cf. John 10:7-18); and an interpretation of the Way of the Cross based on the blessing with the cross. As a concluding reflection, a synthesis of the parish’s Way of the Cross is proposed as a practice of popular spirituality.